Paper modified with ZnO nanorods – antimicrobial studies - Jaisai, Mayuree; Baruah, Sunandan; Dutta, Joydeep (Beilstein Journal of Nanotechnology, 2012)
Paper with antimicrobial properties was developed through in situ growth of ZnO nanorods. The targeted application for this type of paper is in health centers as wallpaper, writing paper, facemasks, tissue paper, etc. The paper was tested on three model microbes, Gram-positive bacteria Staphylococcus aureus, Gram-negative bacteria Escherichia coli and common airborne fungus Aspergillus niger. No viable bacterial colonies or fungal spores could be detected in the areas surrounding test samples of the antimicrobial paper. Gram-negative bacteria Escherichia coli were found to be inhibited in an area that is 239% and 163% the area of the paper sample under different room lighting conditions, i.e., halogen and fluorescent lamp illumination, respectively. For Gram-positive bacteria Staphylococcus aureus the zones of inhibition surrounding the paper samples are 102% and 70%, and for Aspergillus niger, 224% and 183% of the sample area, under similar lighting conditions.
Keywords: antimicrobial; nanorod; paper; photocatalysis; zinc oxide